2021
DOI: 10.3762/bjoc.17.193
|View full text |Cite
|
Sign up to set email alerts
|

Selective sulfonylation and isonitrilation of para-quinone methides employing TosMIC as a source of sulfonyl group or isonitrile group

Abstract: Chemoselective sulfonylation and isonitrilation reactions for the divergent synthesis of valuable diarylmethyl sulfones and isonitrile diarylmethanes starting from easy-to-synthesize para-quinone methides (p-QMs) and commercially abundant p-toluenesulfonylmethyl isocyanide (TosMIC) by using respectively zinc iodide and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as catalysts were developed. The distinguishing feature of this method is that TosMIC plays a dual role from the same substrates in the reaction: as a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Copyright 2018 Royal Society of Chemistry. p-QM [168] has strong dipolar characteristics and a thermodynamic driving force that promotes rearomatization. This reaction provides a convenient route to optically active αsubstituted benzylthioethers, forming the basis of the structures of bioactive molecules [169].…”
Section: • the Catalytic Asymmetric 16-conjugate Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2018 Royal Society of Chemistry. p-QM [168] has strong dipolar characteristics and a thermodynamic driving force that promotes rearomatization. This reaction provides a convenient route to optically active αsubstituted benzylthioethers, forming the basis of the structures of bioactive molecules [169].…”
Section: • the Catalytic Asymmetric 16-conjugate Additionmentioning
confidence: 99%
“…It has been found that quaternary ammonium salts, such as tetrabutylammonium bromide (TBAB), could smoothly promote the reaction of 2,6-methyl-4-[phenyl(tosyl)methyl]phenol with tritylthiol (Table 4, entry 1). p-QM [168] has strong dipolar characteristics and a thermodynamic driving force that promotes rearomatization. This reaction provides a convenient route to optically active α-substituted benzylthioethers, forming the basis of the structures of bioactive molecules [169].…”
Section: • the Catalytic Asymmetric 16-conjugate Additionmentioning
confidence: 99%
“…In this context, Li and co‐workers delineated an asymmetric phase transfer catalyzed 1,6‐conjugate addition of in situ generated para ‐quinone methides with tritylthiol [10b] . Subsequently, 1,6‐conjugate addition of para ‐quinone methides with different sulfonyl sources was independently reported by Liu and Zhu, [10c] Guan and Liu, [10d,e] Das et al ., [10f] Song et al [10g] . to obtain diarylmethyl sulfones.…”
Section: Introductionmentioning
confidence: 99%